If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4x + -9) + 10 = 5x + -5 Reorder the terms: 7(-9 + 4x) + 10 = 5x + -5 (-9 * 7 + 4x * 7) + 10 = 5x + -5 (-63 + 28x) + 10 = 5x + -5 Reorder the terms: -63 + 10 + 28x = 5x + -5 Combine like terms: -63 + 10 = -53 -53 + 28x = 5x + -5 Reorder the terms: -53 + 28x = -5 + 5x Solving -53 + 28x = -5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -53 + 28x + -5x = -5 + 5x + -5x Combine like terms: 28x + -5x = 23x -53 + 23x = -5 + 5x + -5x Combine like terms: 5x + -5x = 0 -53 + 23x = -5 + 0 -53 + 23x = -5 Add '53' to each side of the equation. -53 + 53 + 23x = -5 + 53 Combine like terms: -53 + 53 = 0 0 + 23x = -5 + 53 23x = -5 + 53 Combine like terms: -5 + 53 = 48 23x = 48 Divide each side by '23'. x = 2.086956522 Simplifying x = 2.086956522
| 9x-4=75 | | -15x=1479 | | 9-7x=209-42x | | 3x+30=3 | | -3x+6x^2+5x+9x= | | 300-3P=3P | | 3+7(w+7)+w= | | 11x-3x=14 | | 37=5c-8 | | 11x+7+10x=31 | | 3x^2+5x=-4 | | 12x+24=28x-8 | | -34-4x=4x+22 | | 5xy+3x+4y-5xy= | | 5x^4-6x-8=0 | | 57-3x=10x | | 4x+1y=54 | | 2+7x=56 | | 19p+4q-2p-5q= | | 5[y+2]=4-7y | | 66=(2x+3) | | 10x+20= | | 7y-x+10=180 | | y=1.5+5 | | 5x(x+2)-10=14-4x | | 7x-y+10=180 | | -16+6x=-(1-3x) | | .4x-3=.1(x+30) | | -1/2+2= | | (2x-3)(5x+2)= | | 2(0.3+1)=23-0.1r | | 15(8+2c)=15(3c-5) |